Performance analysis of triple glazing water flow window systems during winter season - Yamac, Halil Ibrahim; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2023)
Water is circulated in the space between glazing as part of the Water Flow Window (WFW) technology. This idea may have an impact on the energy consumption of HVAC (heating, ventilation, and air conditioning) equipment. WFW is commonly used to remove excess heat; the excess heat can be stored. The purpose of this study is to compare the performance of triple glazing WFW under environmental conditions of Turkey during the winter. To compare the electrical energy consumption of the HVAC devices of testing cabinets, three identical testing cabinets with three different glazing types; standard (air-filled) window, WFW system with energy storage tank and domestic water supported WFW system are employed. The Thermal Energy Storage (TES) tank is a water tank that contains two distinct Phase Change Materials (PCM). PCMs are positioned all around and crammed inside water-filled pistol-style tubes. The TES tank volume is 5.675 L (42% water, 46% RT18 HC, 12% RT22 HC). The windows' surface area is approximately 0.3 m2. Visualization of the melting process in the TES tank is obtained with the numerical study. Results show that the consumption ratio of cooling devices can fall under 21% for daytime and heating devices can fall under 79% for nighttime.
Keywords: Solar energy; Water flow window; Thermal energy storage; Phase change process; Computational fluid dynamics